Pengaruh Rasio Keuangan Terhadap Kondisi Financial Disress Di Indonesia - Sherly Andreani, Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this research is to obtain empirical evidence and to analysis about the effects of profitability, leverage, and operational cash flow on financial distress. There are 78 companies that were selected as sample that were selected by using purposive sampling. Data collection techniques used in this research is secondary data that is processed using Eviews version 11 program. The result of this research showed that profitability has a positive and significant on financial distress, operational cash flow has a negative and do not have a significant effect on financial distress, while leverage has negative and significant effect to financial distress. The implication of this research is need to decrease the debt also to increase the income that will prevent the financial distress which will bring a positive signal for investors.